Improving usability in e-democracy systems: systematic development of navigation in an e-participatory budget system. (16th July 2007) - Caceres, Paloma; Rios, Jesus; De Castro, Valeria; Rios Insua, David; , Esperanza Marcos
E-democracy refers to a set of methods to address social issues through the web, possibly by using decision support methodologies to involve citizens in decision-making processes. Participatory budgets, in which citizens participate in budget allocation, are an example. Web applications supporting these processes entail complex interactions in which users communicate their preferences, negotiate alternatives with other participants, etc. Thus, developing web applications may determine the usability and success of an application. To better reflect the paths which may drive users through an application, navigation models have been widely adopted by the web engineering community. HM3 is a navigation modelling method that we apply to the development of a system to support e-participatory budget formation. The system was first implemented without following a navigation modelling method. By comparing these two approaches, we detect navigational issues that could facilitate the user's understanding of decision processes, and suggest guidelines to systematise the development of e-democracy applications.